2016
DOI: 10.7717/peerj.2776
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis reveals that seed-applied neonicotinoids and pyrethroids have similar negative effects on abundance of arthropod natural enemies

Abstract: BackgroundSeed-applied neonicotinoids are widely used in agriculture, yet their effects on non-target species remain incompletely understood. One important group of non-target species is arthropod natural enemies (predators and parasitoids), which contribute considerably to suppression of crop pests. We hypothesized that seed-applied neonicotinoids reduce natural-enemy abundance, but not as strongly as alternative insecticide options such as soil- and foliar-applied pyrethroids. Furthermore we hypothesized tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 65 publications
(95 reference statements)
4
65
1
Order By: Relevance
“…The lack of impact on soil taxa is consistent with the low levels of insecticide residues we found in the soil, which were generally below the threshold for acute toxicity towards arthropods (Douglas & Tooker, 2016;Pisa et al, 2015). However, as mentioned earlier, chronic exposure to the low levels of insecticides that we detected could sub-lethally impact soil-dwelling organisms over time.…”
Section: Non-target Impacts Of Pesticide Seed Treatments On Arthropodssupporting
confidence: 90%
See 1 more Smart Citation
“…The lack of impact on soil taxa is consistent with the low levels of insecticide residues we found in the soil, which were generally below the threshold for acute toxicity towards arthropods (Douglas & Tooker, 2016;Pisa et al, 2015). However, as mentioned earlier, chronic exposure to the low levels of insecticides that we detected could sub-lethally impact soil-dwelling organisms over time.…”
Section: Non-target Impacts Of Pesticide Seed Treatments On Arthropodssupporting
confidence: 90%
“…Additionally, it has been suggested that individual studies of pesticide non-target impacts lack the power to detect effects due to relatively small sample size and high variability in arthropod community datasets (Douglas & Tooker, 2016). A meta-analysis across 20 studies revealed small negative effects [effect size d = −0.30 ± 0.10 (95% confidence interval)] on natural enemy abundance associated with NSTs, with a trend towards soil taxa being more impacted than foliar taxa (Douglas & Tooker, 2016 we expected foliar communities to recover rapidly, as observed by Disque et al (2018) in maize. In contrast, PRC analysis for sticky cards showed increasing deviations from the control community over time in insecticide-treated winter wheat and for all pesticide treatments in maize, with no recovery over the sampling period.…”
Section: Non-target Impacts Of Pesticide Seed Treatments On Arthropodsmentioning
confidence: 99%
“…Many studies have shown the potential for neonicotinoid seed-treatments to harm nontarget organisms such as arthropod pollinators and predators (Prabhaker et al 2011, Seagraves and Lundgren 2012, Lundin et al 2015, Douglas and Tooker 2016. Although neonicotinoid seed-treatments have shown efficacy against many snap bean pests (Nault et al 2004, Koch et al 2005, Reisig et al 2012, this method has not been tested for efficacy or nontarget effects in snap bean systems predominated by E. varivestis prior to this study.…”
Section: Discussionmentioning
confidence: 99%
“…The use of broad‐spectrum insecticides disrupts biological control through direct toxicity to beneficial species and indirectly by changing arthropod communities. While insecticide seed dressings are now widely used in grains and have less pervasive effects on beneficial organisms than conventional high‐volume sprays, they can still adversely impact arthropod predator and parasitoid communities . This is an important issue given the scale at which these insecticides are now being applied.…”
Section: The Future Of Resistance Management In Australian Grainsmentioning
confidence: 99%
“…While insecticide seed dressings are now widely used in grains and have less pervasive effects on beneficial organisms than conventional high-volume sprays, they can still adversely impact arthropod predator and parasitoid communities. 54,55 This is an important issue given the scale at which these insecticides are now being applied. Outside of beneficial arthropods, a lack of economic thresholds for key pests is a major constraint to the adoption of IPM in Australian grain crops and elsewhere.…”
Section: Greater Adoption Of Ipmmentioning
confidence: 99%